Analisis Semiotika Roland Barthes terhadap Legenda Pesut Mahakam pada Masyarakat Kutai - Agustina Agustina; Kukuh Elyana (CV. Alim's Publishing, 2026)
This study aims to explain the meaning contained in the Legend of Pesut Mahakam, especially the denotative, connotative, and mythological meanings, using the semiotic theory developed by Roland Barthes. The Legend of Pesut Mahakam is one of the stories from the people of East Kalimantan that carries cultural value, a moral lesson, and the local understanding that the people of Kutai have. This study uses a descriptive qualitative method with a research type based on reference books. The main source of data comes from the text of the Legenda Pesut Mahakam, which is found in the book Cerita Rakyat Daerah Kalimantan Timur written by Noor dkk. Data is collected by reading and noting down, while data analysis involves identifying signs that have meaning in terms of denotation, connotation, and myth, based on the semiotic theory proposed by Roland Barthes. Research shows that the denotative meaning in the legend describes a series of events experienced by the character, starting from family life, unfair treatment by the stepmother, and the character's transformation into a villain. The implied meaning shows the feelings of unfairness, suffering, loneliness, responsibility, and regret that parents experience. This story shows how the community believes in the origin of Pesut Mahakam, passed down through generations, and includes moral values and local wisdom within it. Therefore, the Legend of Pesut Mahakam is not just a simple folk story, but also a way for the Kutai community to pass down their cultural values. The main keywords are wisdom.